Theorizing resilience-building in the EU's neighbourhood: introduction to the special issue. Issue 7 (3rd October 2021) - Stollenwerk, Eric; Börzel, Tanja A.; Risse, Thomas
ABSTRACT: The EU is surrounded by areas of limited statehood (ALS) and contested orders (CO) in its southern and eastern neighbourhood. Resilience has become a focus of attention in the academic debate on how to successfully deal with ALS and CO. Moreover, resilience-building is a new cornerstone in the EU's foreign and security policy. However, to what extent is resilience a mechanism to cope with ALS and CO? What are the sources of resilience? To what extent does the EU act as a resilience builder or spoiler in its neighbourhood? By presenting a new conceptual framework for analysing the interplay between risks, resilience, and governance breakdown/violent conflict as well as through in-depth empirical evidence, this special issue puts forward three key arguments. First, resilience is a key mechanism to prevent governance breakdown and violent conflict in the EU's neighbourhood. Second, three sources are key in building resilience: Social trust within societies and communities, legitimacy of (state and non-state) governance actors and institutions, as well as effective, fair, and inclusive governance institutions. Third, if external actors, such as the EU, seek to build resilience, they need to factor in long-time horizons, in-depth local knowledge, and a clearly designed strategy.